2022
DOI: 10.3390/diagnostics12081776
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound to Diagnose Pneumonia in Neonates with Fungal Infection

Abstract: With the improvement in survival rates of low-birthweight and very premature infants, neonatal fungal infection, especially fungal pneumonia, is becoming more and more common, but the diagnosis is always challenging. Recently, lung ultrasound (LUS) has been used to diagnose pneumonia in newborn infants, but not fungal pneumonia. This paper summarizes the ultrasonographic features of seven cases of neonatal fungal pneumonia, such as lung consolidation with air bronchograms, shred signs, lung pulse, pleural line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Forty-two consecutive infants with PH from May 2017 to December 2021 were included in this study. According to our clinical practice and literatures, the PH, pneumonia and meconium aspiration syndrome (MAS) can have some similar ultrasound manifestations, such as lung consolidation with air bronchograms (12)(13)(14)(15)(16)(17). Therefore, to determine whether some of the ultrasound findings are specific to PH or not, the controls will include three subgroups, that were pneumonia group, MAS group and normal lungs, respectively.…”
Section: Patientsmentioning
confidence: 99%
“…Forty-two consecutive infants with PH from May 2017 to December 2021 were included in this study. According to our clinical practice and literatures, the PH, pneumonia and meconium aspiration syndrome (MAS) can have some similar ultrasound manifestations, such as lung consolidation with air bronchograms (12)(13)(14)(15)(16)(17). Therefore, to determine whether some of the ultrasound findings are specific to PH or not, the controls will include three subgroups, that were pneumonia group, MAS group and normal lungs, respectively.…”
Section: Patientsmentioning
confidence: 99%
“…A survey showed that pneumonia was the leading cause of death in extremely low birth weight infants, at approximately 22.5% 4 . As an auxiliary tool, lung ultrasound (LUS) has been increasingly used in the diagnosis of pneumonia in recent years and has good diagnostic performance 5–9 . It has become an international consensus method for the diagnosis of neonatal pneumonia 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…4 As an auxiliary tool, lung ultrasound (LUS) has been increasingly used in the diagnosis of pneumonia in recent years and has good diagnostic performance. [5][6][7][8][9] It has become an international consensus method for the diagnosis of neonatal pneumonia. 10,11 Compared with chest X-ray, LUS has the advantages of no radiation, low cost, convenience, speed, and accuracy [12][13][14] and has higher diagnostic efficacy for pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…The infant was followed up for nearly 12 months and experienced normal growth. Over the past decade, LUS has been widely used in the diagnosis and differential diagnosis of neonatal lung diseases [ 3 , 4 ], including neonatal pneumonia [ 5 , 6 , 7 ]. LUS has a number of advantages over CXR; it should serve as a complementary diagnostic method in providing accurate, timely and reliable information [ 8 , 9 ].…”
mentioning
confidence: 99%
“…In addition, the progressive exacerbation of lung disease due to a lack of timely and effective treatment may be one of the reasons for the extensive consolidation and severe atelectasis. Meanwhile, other types of bacterial pneumonitis are sensitive to commonly used antibiotics, respond well to treatment and rarely accumulate atelectasis throughout the lungs, although they also show consolidation on ultrasound [ 1 , 5 , 6 , 7 ]. The problems may be as following: (1) LUS may well detect atelectasis, infiltrations, pneumothorax, etc.…”
mentioning
confidence: 99%